Promoting Religious Dimension in Conflict Resolution: A Review on Mohammed Abu-Nimer Thoughts - Rohman, Muhammad Saifullah (IAIN Surakarta, 2018)
The aim of this paper is to review Mohammed Abu Nimer thoughts on the field of conflict resolution, peace-building, and inter-religious dialogues. As a thinker and practitioner of conflict resolution, he built his work based on his intimate relationship with conflicts. To review his thoughts, this paper traced and observed his main ideas about conflict resolution based on his writings; books, journals, articles, etc. Thus, the findings show that Mohammed Abu Nimer draws upon his thoughts by referring to his religion, Islam. Therefore, Islam as a religion supports peace-building of civilization through its teaching to Muslims. Although Islam became the basis of his works on conflict resolution, it does not mean that he insists it to be used in conflict resolution. His idea is promoting religious dimension in conflict resolution which makes religion as a source of peace rather than a source of conflict. Then, he proves the limit on peace-building and inter-religious dialogue as a means to reach peace between two sides of a conflict. Therefore, peace-building activists should acknowledge and accommodate any possible ways to mediate the conflicting parties in order to make peace.Â Keywords:Religious Dimension, Conflict Resolution, Peace-building, Dialogue